History of Agricultural Engineering School of Thought - Editorial Article (Advanced Engineering Research)
Don State Technical University is a modern, rapidly developing research and educational centre of the Southern Russia. It has extensive international links. DSTU graduates technicalists and carries out research in the area of mechanical engineering and metal processing, production machinery and equipment, machine construction and reliability, instrument making and engineering medicine, robotics and mechatronics, standardization and quality management, environmental engineering protection and life safety, vocational education and psychology, economics and management, electronics and system engineering, computer equipment and data systems.